Nutritional content of lobster (Cherax quadricarinatus) from Lake Toba - Sudibyo, Mufti; Lubis, Khairiza; Prastowo, Puji; Sarifudin, Achmat (Jurnal Biolokus : Jurnal Penelitian Pendidikan Biologi dan Biologi, 2024)
Lobster (C. quadricarinatus) is a type of freshwater shrimp that only live-in fresh water and has a relatively larger body size. Chemical composition of lobster may be affected by its living environment. This study aims to determine the nutritional composition of male and female lobsters from the waters Sukkean Village and the waters of Pangbatan Village, Samosir Regency, North Sumatra Province. Sampling was done by purposive sampling. The dried powder of lobster meat samples (as much as 250 grams per sample) was then tested for mineral content (Ca, K, Mg, Cu, Fe and Zn) and proximate testing (water, ash, fat, protein and carbohydrates). The mineral test results showed that the minerals in each sample were Ca (2430.57-5096.01) mg, K (1.12-1.73) %, Mg (1850.03-2401.53) mg, Cu (10.47-30.08) mg, Fe (20.71-33.25) mg and Zn (74.82-78.58) mg. While the results of the proximate test showed that the contents of water, ash, fat, protein and carbohydrates were respectively 5.12-7.88%, 6.48-7.38%, 3.27-4.17%, 80.61-83.29%, and 0. 53-1.84%. Based on the results obtained, the highest nutritional content of lobster meat from the mineral and proximate tests was calcium (Ca) and protein.